Estimation and Comparative Analysis of Cohort and Period Total Fertility Rates in Bangladesh - Hossain, Md Mowazzem; Islam, Md Nurul; Shah, Md Asaduzzaman; Hossain, Md Golam; Mamun, Abu Sayed Md. Al; Mondal, Md Nazrul Islam (Asian Journal of Population Sciences, 2026)
Background: Fertility rates are one of the most important factors in understanding demographic change. Issues related to population planning strategy are generated in Bangladesh because of its high fertility rates, still just marginally above the replacement rates. There is very little literature available related to Bangladesh, because the decrease in cohort fertility rates in developed countries has been widely reported. Focusing on parity progression and the process of family formation, this analysis examines the magnitude of the cohort fertility rate (CFR) and the total cohort fertility rate (TFRc). Methods: This research used BDHS 2017-18 as its data source. Fertility was analyzed with parity progression ratio (PPR). The length of time between births and the chance of upgrading with increasing birth order are important factors that have been evaluated. In exploring these trends, PPR values are evaluated with three approaches: by the proportion of women with at least one child ever born (CEB), the calculated TFRc values, and direct PPR values. Several estimates have been created for women in general and the married ones. Results: The results reveal that the total fertility rate of Bangladesh remains a slight above the replacement rate. The TFRc for all women was 2.30, whereas for married women, the TFRc was 2.45, which matches the generally given TFR of 2.3 in BDHS 2017-18. Notwithstanding the total fertility rate gradually dropping, women are still mostly moving up from lower orders to higher orders of fertility, indicated by PPR study research. Conclusions: Parity-based approaches such as PPR are important in understanding fertility change, as underscored in this study. While fertility is lower, it is still above replacement levels, and hence FP programs need to be strengthened, RH services need to be expanded, and families need to aim for small family sizes through policies that incorporate the use of PPR in fertility estimation.